Living on death row : the psychology of waiting to die - Toch, Hans; Acker, James R., 1951-; Bonventre, Vincent Martin (American Psychological Association, 2018)
"The contributors to this book provide insights into the multiple and layered dimensions of death row confinement. Multiple audiences will find something of value in the varied chapter offerings. Mental health professionals will gain greater familiarity with the conditions confronting prisoners under sentence of death. Corrections officials will learn more about research that has focused on the institutional behavior of prisoners under sentence of death. Members of the legal community--lawyers and judges--and policy advocates will benefit from the insights provided by mental health professionals, corrections personnel, and other chapter authors. The book is organized into four parts comprising 12 chapters. Part I provides an introductory survey of the physical environment and the political and legal landscape of death row, as well as of the treatment of death row inmates. Part II explores constitutional questions that arise in challenges to death row and to the treatment of death-sentenced inmates, as well as the legitimacy and wisdom of the policies that segregate those inmates from others and subject them to long-term solitary confinement. Part III addresses the question, how can a person who has been locked away for extended periods of time under the most adverse possible conditions go about mitigating the pain, ameliorating the stress, and transcending the limited opportunity structure of his stultifying environment? Part IV features the perspectives of individuals who spent years in prison under sentence of death before justice system officials acknowledged their wrongful conviction for capital murder and released them from custody to reenter free society."--Preface (PsycINFO Database Record (c) 2018 APA, all rights reserved)